Exploring the Implementation and Impact of Community Policing Strategies in Indonesia: A Case Study of Jakarta - Ryno Novianto (Journal of Public Representative and Society Provision, 2023)
An growing number of police agencies are implementing a strategy called "community policing," which seeks to improve law enforcement by fostering trust and communication between police and the communities they serve. This study examines the implementation and outcomes of community policing tactics in Jakarta, Indonesia, through the lens of a case study analysis. The study found that while community policing can have a positive impact on various aspects of community life, there are challenges and limitations to its implementation in Jakarta, including the lack of resources and funding, the hierarchical structure of the police force, and the lack of public awareness and understanding of community policing. The study recommends that Jakarta's policymakers and law enforcement agencies allocate adequate resources and funding to community policing initiatives in order to address these problems.